AUSTRALIAN SPORTS DIPLOMACY TOWARDS ASIA-TAKE THE BASKETBALL ENGAGEMENT AS AN EXAMPLE - Xia, Menghu; Xia, Ting (ASEAN Journal of Sport for Development and Peace, 2023)
This study aims to analyze Australian sports diplomacy toward Asia. According to the sports diplomacy expert Dr. Stuart Murray, "Sports-diplomacy exchanges can promote international understanding and friendship, as well as dispel stereotypes and prejudices." Australia is an Oceanian state well-known for its sports excellence and culture. Because of its geographical location and history, Asian partners have never been neglected or forgotten by the administrators since Britain colonized the land in 1788. Over the years, there has been a clear trend that Australia is employing its sports diplomacy and increasingly engaging with Asia. This study uses the Australian basketball engagement towards Asia as an example of its sports diplomacy towards Asia. Reviewing the Australian government's official guiding documents,' Australia in the Asian Century White Paper, Australian Sports Diplomacy Strategy 2015-18, Sports Diplomacy 2030, the authors conclude that Australia is increasingly engaging with Asia with its sports diplomacy, including basketball diplomacy. As a result, Australia has acquired a better international reputation and international relations in Asia. Hence, sports diplomacy has become a valuable tool for Australia to exert soft power and enhance international relations in Asia.